I'm a big sister - Cole, Joanna; Chambliss, Maxie (New York : Morrow Junior Books, 1997)
A sister enumerates the joys of welcoming a new baby to the family and the advantages of already being "big."
Keywords: Sisters -- Fiction; Babies -- Fiction; Siblings -- Fiction; Infants -- Fiction; Sisters -- Fiction; Infants -- Fiction; Easy reading material